Libertinism during Restoration Era and the Liberation of a Restricted Sexuality - Gurung, Golman (Journal of Development Review, 2023)
This paper deals basically with defining libertinism as a freedom movement giving attention to the rise of theatre activities during the of Restoration Era. In addition to this, the evolution of libertinism from pre-Enlightenment Era to how it was revived by the Court Wits during the regime of King Charles II of England is reviewed. It views that the sexuality was defined in consonance with someone’s vested interest of maximizing the pleasure of the self and of controlling others thereby giving rise to the guiding principles, norms, morality, law and policies on it. It reviews half a dozen of books on libertine sexuality with particular reference given to two selected Restoration libertine playwrights William Wycherley and Thomas Shadwell, and shows how bourgeoisie sexual morality came to blast caused by its complete disregard to one’s release of private pleasure. It finds that the libertine dramas have helped not only to expose people’s sexuality naturally in the public, but also to redefine sexuality in a quite open and unrestrained manner. If finally concludes that the established and seemingly rigid normative standards, which aim to demolish the real human sexuality, are also subject to change.